Impact of COVID-19 social distancing recommendations on pulmonary function, nutritional status, and morbidity in patients with cystic fibrosis - Maria Amélia Bagatini; João Paulo Heinzmann-Filho; Fernanda Maria Vendrusculo; Leonardo Araújo Pinto; Márcio Vinícius Fagundes Donadio (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To evaluate the impact of COVID-19 social distancing recommendations on nutritional status, pulmonary function, and morbidity in patients with cystic fibrosis (CF). Methods: A retrospective cohort study including patients older than six years with a diagnosis of CF was performed. Demographic and clinical data, anthropometric measurements, pulmonary function, days of antibiotic use, and length of hospital stay were recorded. Variables were recorded at three time points relative to the baseline for implementation of social distancing measures: T-1 (14 months before implementation), T0 (baseline), and T1 (14 months after implementation). Delta (Δ) was calculated for each period: Δ1 (pre-pandemic T0-T-1) and Δ2 (pandemic T1-T0). Results: The study included 25 patients, with a mean age of 11.7±4.3 years. The mean forced expiratory volume in the first second (FEV1) was 85.6±23.6%, and body mass index (BMI) was 17.5±3.0 kg/m2. When comparing the two periods (Δ1 and Δ2), there was a significant increase in the FEV1/forced vital capacity (FVC) ratio (p=0.013) and in the forced expiratory flow between 25 and 75% of vital capacity (FEF25-75%) (p=0.037) in the pandemic period. There was also a significant reduction (p=0.005) in the use of antibiotics in the pandemic period compared with the pre-pandemic period. The Δ1 and Δ2 values did not differ significantly for BMI, FEV1, or length of hospital stay. Conclusions: COVID-19 social distancing recommendations had a positive impact (decrease) on morbidity (use of antibiotics) and small airway obstruction (FEF25-75%) in patients with CF.